2011
DOI: 10.1093/sleep/34.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Related Changes in Blood Pressure in Hypocretin-Deficient Narcoleptic Mice

Abstract: Chronic lack of hypocretin signaling may entail consequences on blood pressure that are potentially adverse and that vary widely among wake-sleep states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
102
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 40 publications
9
102
2
Order By: Relevance
“…2A also indicates that ABP and HR increased upon awakening significantly less in ORX-ATX3 mice, which lack the orexin neurons, than in wild-type mice. 36 This observation fits with previous evidence 38 that ABP was higher during sleep, but not during wakefulness, in either young adult ORX-ATX3 mice lacking orexin neurons 37 or young adult orexin knockout (ORX-KO) mice lacking orexin peptides 40 than in wild-type mice. There is substantial evidence that orexin neurons co-release dynorphin and glutamate, and more contrasting evidence that at least some of these neurons co-express nociceptin/orphanin FQ, galanin, neurotensin, and GABA (cf.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepsupporting
confidence: 90%
See 2 more Smart Citations
“…2A also indicates that ABP and HR increased upon awakening significantly less in ORX-ATX3 mice, which lack the orexin neurons, than in wild-type mice. 36 This observation fits with previous evidence 38 that ABP was higher during sleep, but not during wakefulness, in either young adult ORX-ATX3 mice lacking orexin neurons 37 or young adult orexin knockout (ORX-KO) mice lacking orexin peptides 40 than in wild-type mice. There is substantial evidence that orexin neurons co-release dynorphin and glutamate, and more contrasting evidence that at least some of these neurons co-express nociceptin/orphanin FQ, galanin, neurotensin, and GABA (cf.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepsupporting
confidence: 90%
“…However, the finding of similar ABP derangements in ORX-ATX3 mice and ORX-KO mice with respect to wild-type mice suggests that the lack of orexin release, as opposed to the lack of other transmitters co-released by orexin neurons, is sufficient to alter ABP during sleep. 38 These data, 38 as well as those reported in Fig. 2A, 36 were obtained on mice with a "pure" C57Bl6/J genetic background.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepsupporting
confidence: 57%
See 1 more Smart Citation
“…Our findings are similar to those reported previously in rats (Ootsuka et al, 2009, Blessing et al, 2012. Thus, the present data is consistent with the view that the ultradian alternation of rest-active states is a fundamental part of animal life (Aschoff and Gerkema, 1985, Ootsuka et al, 2011, Blessing et al, 2012, 2013.Previous studies, using EEG-based wake-sleep scoring, show robust changes in behavioural and physiological parameters upon waking (Mochizuki et al, 2006, Zhang et al, 2007, Bastianini et al, 2011, Lo Martire et al, 2012, Silvani et al, 2014, Bastianini et al, 2015. Zhang and colleagues performed simultaneous recording of different behavioural and physiological parameters in mice, including EEG and food intake, observed that eating occurs approximately 15 min after waking (Zhang et al, 2007).…”
supporting
confidence: 93%
“…The effects of genetic manipulation on cardiovascular function have been studied in both orexin peptide knockout mice and orexin neuron-ablated orexin/ataxin-3 transgenic mice and rats, leading to a conflicting data set regarding the effects on heart rate and blood pressure (Kayaba et al, 2003;Schwimmer et al, 2006;Zhang et al, 2006;Schwimmer et al, 2010;Bastianini et al, 2011). The relevance of either of these genetic models to the pharmacological antagonism of orexin receptors in humans is unknown.…”
Section: B Orexin Influences On Peripheral Physiologymentioning
confidence: 99%